The Influence of Knowledge and Investment Risk on Student Interest to Invest with Investing Attitudes as Mediating Variable - Nicholas Arvin Ompusunggu; Eka Ardhani Sisdyani (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
The research focuses on the interests of students, especially the younger generation who already have an interest in investing in the capital market. This study aims to analyze and provide empirical evidence regarding the effect of knowledge and investment risk on student interest in investing mediated by investment attitudes. The research population is students of the Accounting Department, Faculty of Economics and Business, Udayana University. The sample collection method was probability sampling with a simple random sampling technique and 156 students were selected as research samples. Data were analyzed using multiple linear regression analysis techniques and Sobel test as a mediation test. The results of the study found that investment knowledge had no effect on student interest in investing in the capital market, while investment risk had a positive effect on student interest in investing in the capital market, in addition to investing attitudes had a positive effect on student investment interest. The results of this study also prove that investment attitudes are not able to mediate the effect of knowledge and investment risk on student interest in investing in the capital market.